Space-borne Air Quality Monitoring of Nitrogen dioxide (NO2) over Karachi and Lahore using Remote Sensing Tools - Rabbia Rehmat; Lubna Rafique; Muhammad Irfan; Samreen Riaz Ahmed; Altaf Hussain Lahori; Aqsa Muhammadi; Muhammad Taha; Sergij Vambol; Mykhailo Shulga (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
In this study, we used Sentinel-5P TROPOMI satellite data to examine the NO2 and gas concentrations in the cities of Lahore and Karachi, Pakistan, and to use environmental valuation methods that focus on air quality problems. Furthermore, the causes and main sources of NO2 are discussed with its effect on the environment and the health of humans. This study examines the correlation between the tropospheric NO2 collected from the recently launched Sentinel-5 Precursor, a low-earth-orbit atmospheric mission dedicated to observing air pollution and outfitted with the spectrometer TROPOMI (Tropospheric Monitoring Instrument). The average amount of NO2 that was gathered between May 2018 and May 2022. The results showed higher levels of NO2 concentrations were recorded in both, Karachi and Lahore. The concentrations exceed the WHO standard levels for NO2 in ambient air. The NO2 concentrations in Karachi ranged from 3.0e-6 mol/m2 being the minimum average concentration to 4.0e-1 mol/m2 being the maximum concentration. However, in Lahore, the minimum average value of NO2 was ranging from 4.0e-5 mol/m2 to 5.5e-1 mol/m2 as the maximum average, which was higher than the minimum and maximum values of Karachi. The study also revealed that the NO2 concentrations measured for both cities were higher than the WHO's yearly limit threshold, which is 53 ppb/year. Thus, it was crucial to take action to address this issue before it poses a severe risk to the local people. This study's identification of the key regions with the greatest NO2 concentrations will aid in understanding the significance of satellite data for monitoring NO2 concentration. Thus, the originality of the study lies in the fact that using the example of Karachi and Lahore, the dynamics of the deterioration of the environmental situation was revealed, and the main reasons for what was happening were also established. In this case, an available tool was used - remote sensing tools. The competent authorities can assist this study in managing and regulating the air quality in the most densely populated areas.